Management of Dietary Education for Children with Thalassemia at the Thalassemia Polyclinic - Bakar, Shabilla Fasa Noor; Yudianto, Kurniawan; Eriyani, Theresia (Universitas Padjadjaran, 2026)
Dietary education in thalassemia major is often neglected due to high nursing workloads. This case report evaluates a structured dietary education intervention using management frameworks to address this gap. The methods are a descriptive study was conducted on a family with three siblings diagnosed with thalassemia major and severe hyperferritinemia. The 3M (Man, Method, Material) analysis identified primary barriers: high procedural workload, lack of SOPs, and absence of educational media. Consequently, a POAC (Planning, Organizing, Actuating, Controlling) intervention using digital videos and leaflets was implemented to overcome these constraints. The results that the intervention effectively bypassed clinical time constraints. Family health literacy improved substantially, with dietary knowledge scores increasing from 2 out of 5 to a perfect 5 out of 5, sustained over a five month follow-up. Behavioral changes in meal preparation were reported, although immediate serum ferritin reduction was not yet observed. Structured education utilizing digital media effectively bridges the gap between patient needs and limited nursing resources. Integrating digital tools into routine practice and establishing SOPs are recommended to ensure comprehensive management and improve long-term patient outcomes.